2003
DOI: 10.1128/jcm.41.4.1664-1672.2003
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae Carriage in Children Attending French Day Care Centers: a Molecular Epidemiological Study

Abstract: The nasopharyngeal Haemophilus influenzae flora of healthy children under the age of 3 years attending day care centers in three distinct French geographic areas was analyzed by sampling during two periods, spring 1999 (May and June) and fall 1999 (November and December). The average carrier rate among 1,683 children was 40.9%. The prevalence of capsulated H. influenzae carriers was 0.4% for type f and 0.6% for type e. No type b strains were found among these children, of whom 98.5% had received one or more do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 32 publications
(36 reference statements)
3
32
1
Order By: Relevance
“…The incidences of ␤-lactamase-positive H. influenzae strains isolated from the nasopharynx vary greatly among countries, from 1.8% in The Netherlands (26) to 20% in Portugal (7) and 47.4% in France (4). In this study, only five isolates of H. influenzae (3.7%) produced ␤-lactamase.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The incidences of ␤-lactamase-positive H. influenzae strains isolated from the nasopharynx vary greatly among countries, from 1.8% in The Netherlands (26) to 20% in Portugal (7) and 47.4% in France (4). In this study, only five isolates of H. influenzae (3.7%) produced ␤-lactamase.…”
Section: Discussionmentioning
confidence: 56%
“…Despite the high consumption of ␤-lactams in Poland, the frequency of ␤-lactamase-positive H. influenzae strains isolated from lower RTIs remains low (16). The data from a recent multicenter study showed that 0% of encapsulated and 4.4% of nontypeable H. influenzae strains isolated between 1996 and 2001 from cases of community-acquired lower RTIs in Poland were ␤-lactamase (4,26). In a previous study in England (14), the overall H. influenzae type b nasopharyngeal carriage rate among children 1 to 4 years old was 3.97% before routine vaccination was introduced, but following the introduction of vaccination, the rate of H. influenzae type b (Hib) isolation decreased to 0.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, understanding the dynamics of H. influenzae colonization forms the foundation for understanding the natural history of diseases caused by this bacterium. While previous studies have investigated H. influenzae pharyngeal colonization among healthy adults (4) and among individuals at risk for H. influenzae infections, such as children attending day care centers (8,14,56), patients with cystic fibrosis (49), and adults with COPD (38,43), no previous reports have documented colonization with H. haemolyticus in population-based studies of healthy adults. Pharyngeal colonization with nonhemolytic H. haemolyticus has only recently been described (16,39).…”
Section: Discussionmentioning
confidence: 94%
“…Among H. influenzae isolates, we observed a high degree of (3,27). Contrary to what was observed for pneumococci, no single dominant clone was identified, but clones with different fitness properties were observed.…”
Section: Discussionmentioning
confidence: 90%